Fairy Tales : A touch-and-feel playbook (London : Ladybird books, 2021)
Say hello to your favorite fairy tale characters from Cinderella to Little Red Riding Hood! With textured patches to touch, feel and explore, this bright and sturdy board book with grabbable tabs will encourage young children from birth upwards. High-contrast colors and touch-and-feels stimulate a baby's senses, while encouraging interaction and play"--Publisher's description.
Keywords: Board book; English - fiction; Picture - book